The Effect of Labor Movement or Migration on the Indonesian Economy - Manurung, Mahlina Putri; Hutabalian, Relli Anisma; Matondang, Khairani (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
This article examines the impact of migration and labor movement on the Indonesian economy, highlighting key areas such as economic growth, employment, consumer spending, and remittances from migrant workers. Labor migration has been a significant aspect of Indonesia’s economic structure, affecting both the domestic labor market and the broader economic landscape. The article explores how the outflow of Indonesian workers abroad influences employment dynamics, with some sectors benefiting from reduced domestic competition, while others experience labor shortages. Additionally, remittances from migrant workers play a crucial role in boosting household income, contributing to consumer spending, and stimulating local economies in various regions. The study also delves into the Indonesian government's policies and initiatives aimed at managing labor migration, including the protection of migrant workers' rights, improving workforce skills, and addressing challenges related to illegal migration. By analyzing the multifaceted impacts of labor migration, this article provides a comprehensive understanding of its role in shaping Indonesia's economic development. The findings suggest that while labor migration offers significant benefits through remittances and economic growth, challenges such as labor exploitation and brain drain require effective policy responses to maximize the positive impacts on the national economy.